HUBUNGAN PERSEPSI INFORMASI PASIEN TERHADAP PERAN PERAWAT SEBAGAI EDUCATOR DI PUSKESMAS - Sri Wahyu Gusti Fajri; Erwin Erwin; Yesi Hasneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Perception is a process that arises due to sensation, where sensation is the activity of feeling or the cause of the emotional state. The perception of each individual is different, the perception is influenced by several factors, the factors that influence the perception are divided into two, namely internal factors and external factors. Nurses as the vanguard of health care providers in hospitals and health centers are required to be able to to act as the educators. This study aims to determine the relationship of factor information related to the perception of patients to the role of nurses as educators in the puskesmas. This study used a descriptive design correlation with the cross sectional approach. The research sample was 97 respondents with accidental sampling techniques.  This study uses questionnaires that have previously been conducted tests of validity and reliability.  There was no significant  relationship  between  information  (pvalue = 0, 333) . Information factors not related to the role of nurses as educators in puskesmas.Key words: Information; Nurse’s Role as Educator;  Perception